A study on the effectiveness if In-House Union SESB Headquarter in Kota Kinabalu / Bibianah Nasir and Rachel Benedict - Nasir, Bibianah; Benedict, Rachel (2013)
The declining numbers of unionized workers had led to the research on different dimensions of what perceived as effective union. This research examined the effectiveness and also factors associated with the effectiveness of in house union in SESB Headquarter Kota Kinabalu. Data were gathered through a questionnaires (n - 103) and analysed using correlation test. The result suggest that, the communication within union, power of the union, union as source of information and union responsiveness to members have significant relationship with union effectiveness. Finally, power of the union was the most important key that should be look into by the in-house union as it is the having the strongest correlation with union effectiveness.